Measuring Distance Between Two Features By Using Stereophotogrammetry Principle - Awaldastiana, Dananjaya
Stereophotogrammetry is a non-contact measurement method that uses two cameras to get image’s depth perception from two corresponding images. Stereofotogrammetry has several advantages, which is fast, cheap, and have high accuracy. This final project research is conducted to develop an object’s dimensions measurement methodology by using stereophotogrammety. This research uses MATLAB and its buit-in features and toolboxes. The processes include image acquisition, which is carried out to acquire calibration and object’s images; Camera calibration to estimate camera’s parameters as data that utilized for estimating object’s real world coordinate; Image processing is conducted to reconstructing 3D of object’s image and acquiring object’s edge point cloud; And to measure object’s dimensions, object’s edge is to defined as a line and/or point then processed to get the distance between these two kinds of features. Stereophotogrammetry based measurement’s errors are contributed by a few factor such as image quality and features selection in measuring process.